Effect of Cynoglossum zeylanicum (Vehl ex Hornem) Thunb. Ex Lehm on Oral Glucose Tolerance in rats - M. Anitha, G. Sakthidevi, S. Muthukumarasamy and V. R. Mohan (Journal of Applied Pharmaceutical Science)
The effect of ethanol extract of whole plant of Cynoglossum zeylanicum on Oral Glucose Tolerance was determined. Ethanol extract of Cynoglossum zeylanicum were evaluated for Oral Glucose Tolerance Test (OGTT) in normal and alloxan induced diabetic rats. Oral administration of ethanol extract at doses of 100 &150mg/kg body weight shows that the extract promote glucose uptake. These results suggest that the ethanol extract of Cynoglossum zeylanicum whole plant will be useful in the treatment of impaired oral glucose tolerance.
Keywords: OGTT, Diabetic, Jathakkai, Flavonoid, Cynoglossum zeylanicum.